Integrated management of termite in wheat through organic amendments and seed treatment - Bhatt, N A; Borad, P K (Indian Journal of Plant Protection, 2020)
A field experiment was conducted for two years at Agronomy farm, B A College of Agriculture, Anand Agricultural University, Anand in randomized block design with nine treatments and three replications to formulate integrated pest management strategy for termite infesting wheat. The effective and economical treatments consisting of organic amendment as castor cake @ 1 ton/ha + seed treatment with fipronil 5 SC 5 ml/kg seed (ICBR: 1:7.36) or castor cake @ 1 ton/ha + seed treatment with chlorpyriphos 20 EC 4 ml/kg seed (ICBR: 1:7.51) or organic amendment as neem cake @ 1 ton/ha + seed treatment of fipronil 5 SC 5 ml/kg seed (ICBR: 1:3.50) were found highly effective components for the management of termite in wheat crop. There was no deleterious effect of the treatments on seed germination and number of tillers per plantin wheat.